Decimator systolic arrays design space exploration for multirate signal processing applications - Shoukry, Mohammed; Gebali, Fayez; Agathoklis, Panajotis (IET circuits, devices & systems, 2019)
This study presents a new systolic array structure for a decimator that merges the antialiasing finite impulse response (FIR) filter with the downsampler. The development of the structure is based on a systematic methodology. Using this methodology, a dependence graph for the decimator was obtained that combined the antialiasing filter and the downsampler. Different data scheduling and projection operations were developed to obtain different proposed designs. Six systolic array design options were obtained and evaluated. The fastest design was selected for hardware implementation and compared with the other two well known decimator designs; namely, conventional design, in which the antialiasing filter is followed by a downsampling and the polyphase design, in which a commutator is followed by the polyphase antialiasing filter. Field-programmable gate array implementations for the proposed and the other two designs confirm that the proposed decimator implementation outperforms in terms of area, speed, and power as the decimation factor increases regardless of the number of FIR filter coefficients.